Identification of miR-499a-5p as a Potential Novel Biomarker for Risk Stratification in Endometrial Cancer - Ravegnini, Gloria; De Leo, Antonio; Coada, Camelia; Gorini, Francesca; de Biase, Dario; Ceccarelli, Claudio; Dondi, Giulia; Tesei, Marco; De Crescenzo, Eugenia; Santini, Donatella; Corradini, Angelo Gianluca; Tallini, Giovanni; et al. (Frontiers in Oncology, 2021)
Introduction. The TGCA project identified four distinct prognostic groups in endometrial carcinomas (ECs) among which two are correlated with an intermediate prognosis: the MisMatch Repair deficient (MMRd) and the No Specific Molecular Profile (NSMP) groups. The two groups represent a heterogenous subset of patients frequently harboring CTNNB1 alterations with distinctive clinicopathologic features. The study aimed to evaluate the miRNAs expression in ECs to identify potential biomarkers of prognosis. Methods. We analyzed miRNA expression in 72 ECs classified as MMRd or NSMP including 15 ECs with CTNNB1 mutations. In the discovery step, miRNAs expression was evaluated in 30 cases through TaqMan miRNA arrays. Subsequently, 4 miRNAs were validated in the total cohort of ECs. The data were further tested in the TGCA cohort and correlations with overall survival (OS) and progression free interval (PFI) were evaluated. Results. miR-499a-3p and miR-499a-5p resulted over-expressed in CTNNB1 mutant ECs in patients at intermediate risk. Similarly, in the TGCA cohort, miR-499a-3p and miR-499a-5p were differentially expressed between CTNNB1 mutant and wild type patients (p<0.0001). Patients with low miR-499a-5p expression showed longer OS (p=0.03) in NSMP cohort. By combining miR-499a-3p and -5p expression level with the CTNNB1 status, ECs with CTNNB1 mutation and lower 499a-5p expression showed better OS compared with the other subgroups (p=0.03), among the NSMP patients. Conclusion. Our results suggest that combination of CTNNB1 status and miR-499a-5p allows a better stratification of NSMP patients and could promote a personalization of the treatment in intermediate risk patients